PENGARUH STRATEGI PRODUK TERHADAP KEPUASAN KONSUMEN DI RUMAH MAKAN CECE, KECAMATAN KEI KECIL, KABUPATEN MALUKU TENGGARA - Benedictus R. Khuana (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to analyze the effect of product strategy on consumer satisfaction at the Cece Langgur Restaurant, Kei Kecil District, Southeast Maluku Regency. Based on the results of data analysis, the results of the linear regression test are obtained, the regression equation is Y = 12.858 + 0.746X. This equation states that when the Product Strategy variable is 0, then Consumer Satisfaction has a value of 12,858, and a positive value of 0.746 found in the regression coefficient of the independent variable (product strategy) illustrates that the direction of the relationship between the independent variable (product strategy) and the dependent variable (customer satisfaction) is unidirectional, where every increase of one unit of product strategy variable will cause an increase in customer satisfaction by 0.746. Based on the results of the t test, it can be concluded that tcount is greater than ttable, so H1 is accepted and H0 is rejected. From the results of the tcount calculation of 6,107 above compared to ttable (df = 43), namely 1.6810, a significant level of 5%, so tcount > ttable, then H1 is accepted and H0 is rejected. Meanwhile, the Determinant Coefficient test explains that the influence of the Product Strategy Variable (Variable X) on the Consumer Satisfaction Variable (Variable Y) is 46.5% and the remaining 53.5% is influenced by other variables not included in this study.